Compounding Pharmacy Restoration as a Current Healthcare Priorit - A. Z. Farrakhov (Регуляторные исследования и экспертиза лекарственных средств)
The matter of restoring the system of compounding pharmacies is actively discussed by members of the medical and pharmaceutical communities as well as government officials at various levels. This interview presents the views of Ayrat Z. Farrakhov, Head of the Working Group for the Restoration of Compounding Pharmacies of the State Duma Committee on Health Protection, representative to the 8th State Duma of the Federal Assembly of the Russian Federation, member of the State Duma Committee on Budget and Taxes, Vice-President of the National Medical Chamber Medical Community Union, Doctor of Medical Sciences, Associate Professor, and Honoured Doctor of the Republic of Tatarstan.